Soil Drenching with Silicon Improves the Adaptive Response of Tobacco Cultivation under Excess Water Condition - Almansyah Nur Sinatrya; Sigit Soeparjono; Tri Candra Setiawati (Caraka Tani: Journal of Sustainable Agriculture, 2022)
Tobacco variety H382 was a cigar type tobacco that has a high economic value and potential as export trade commodity in Indonesia. The development stage of tobacco was very sensitive to water stress, like the water excess. Silicon was one of the most abundant elements in earth crust and has a role in water stress reduction to the plant. The objective of this study was to determine the response of tobacco crop variety H382 with the application of silicon fertilizer to adapt in waterlogging stress condition. This study used a factorial randomized block design with first factor was silicon fertilizer (0, 0.15, 0.30 and 0.45 ml) and second factor was excess water stress treatments (50% to 70%, 70% to 90%, 90% to 110% and 110% to 130% of field capacity). All treatments were replicated three times. The results showed that the addition of 0.45 ml silicon fertilizer to waterlogged tobacco crop could escalate the adaptive response of plant to cope with stress; seen from the increasing of the opened stomata, aerenchyma formation and the chlorophyll content of tobacco crop under excess water stress compared to control. Silicon supplementation improves the water availability in root surroundings and repairs the root architecture; thus, lead to a better hydraulic conductivity of the root for water and nutrient intake. Furthermore, authors found that the application of silicon fertilizer helped tobacco crop variety H382 improve plant adaptability to deal with excess water stress.